Simple and smart—promoting consumers’ willingness to consume and offer expired but still edible food through an informational intervention - Schmidt, Karolin (Frontiers in Psychology, 2025)
IntroductionIn order to curb household food waste in industrialized countries such as Germany, appropriate interventions are needed to encourage consumers to adopt various food-waste-prevention practices, for example, with respect to expired food. The main objective of the present study was to evaluate the effects of an informational intervention. This intervention provided problem and action knowledge about the environmental problem of household food waste and consumers’ engagement in food-waste-prevention consumption practices referring to expired food. The study focused on consumers’ willingness to consume and to offer expired but still edible food. Additionally, it examined the psychological mechanisms underlying these effects.MethodsWe conducted an online survey in a sample of German consumers (N = 558). For the survey, participants were randomly assigned to an experimental group (EG, which was given the informational intervention) or a control group (CG, which was given a placebo intervention).Result and discussionIn line with our expectations, we found that EG participants reported a stronger personal norm for the consumption of expired but still edible food as well as lower perceived health risks when consuming expired food than CG participants did. Furthermore, EG participants were significantly more willing to offer expired but still edible food to others in a hypothetical food-choice experiment than CG participants were. A mediation analysis implied this intervention effect to be mediated by participants’ personal norm and their perceived health risks. Taken together, the present study provides valuable insights for an intervention designed to prevent household food waste by focusing on relevant consumption practices and going beyond a consumer-focused intervention perspective.